Family Socioeconomic Status Influences Academic Burnout Among College Students: A Systematic Study - Zahra, Syekha Aulia Mutia; Hidayat, Dede Rahmat (Bisma The Journal of Counseling, 2024)
Academic burnout is a common phenomenon that can affect students in a variety of situations. One of the causes of academic fatigue is the family's socio-economic status. This research aims to find out how family socio-economic status influences academic burnout. This research is a systematic research study. The data collection method used in this research is literature study with international databases, namely SpringerLink, AscoPubs, AtlantisPress, and Frontiers.orgArticles from various databases were selected using PRISMA, focusing on those published between 2013-2023 that included keywords like family socioeconomic status and academic burnout. There were 6 articles that met the criteria set from initial findings of 1,071 articles. Next, the article was analyzed in three stages, namely, reading and understanding the contents of the article, extracting the reading results and summarizing them in a table, and analyzing and concluding the findings. The results of the analysis found that the impact of low family socio-economic status is a lack of access to development resources, namely finances and time spent with parents, less capital expenditure for self-development, the emergence of rejection, running away and rebellious behavior, so that in the end individuals experience academic burnout. It can be concluded that socio-economic status is an important factor in predicting academic burnout. The latest research highlights the need to better integrate family socioeconomic status into studies, exploring its impact on academic burnout and developing prevention methods based on these influences.